Teachers' Attitude Towards ICT and its Usage as Predictors of Senior Secondary Students’ Performance in Physics - Jinadu, Afeez Tunde; Amusa, Jamiu (PJDOL, 2025)
The study investigated teachers' attitude towards ICT and its usage as predictors of senior secondary student performance in Physics. The study employed a correlation survey to sample 105 respondents drawn from five schools. Three instruments; TAIQ (r=0.86), TIUQ (α = 0.78) and PAT (r=0.83) were employed. Pearson correlation and multiple regression analysis were employed. Teacher ICT attitudes and ICT usage correlate positively with students' achievement in Physics {r = 0.542; r = 0.521 both p < 0.05). There is a combined influence of teachers’ ICT attitude and ICT usage on students' achievement in Physics (R² = 0.565). Independently, teachers' attitudes (β = 0.346) influenced student achievement in physics more than ICT usage (β = 0.268). The study established the predictive ability of teachers ICT attitude and ICT usage for enhanced students' academic achievement in physics. Therefore, there should be provision of improved access to ICT facilities in schools and teachers should be encouraged to form positive attitude towards ICT.